Hot Topics in Pediatric Infectious Disease: 2012 - Vinall, Phil (MD Conference Express, 2012)
Children infected with Mycobacterium tuberculosis have a significant risk of developing tuberculosis (TB) and therefore can benefit from preventive therapy and new diagnostic techniques. This article discusses the advantages and disadvantages of some new diagnostic techniques being used to test children for TB.